Eating flowers? Exploring attitudes and consumers' representation of edible flowers. (October 2017) - Rodrigues, H.; Cielo, D.P.; Goméz-Corona, C.; Silveira, A.A.S.; Marchesan, T.A.; Galmarini, M.V.; Richards, N.S.P.S.
Abstract: Edible flowers have gained more attention in recent years thanks to their perceived health benefits. Despite this attention, it seems that edible flowers are not popularized for consumption in South America, being considered unfamiliar for some cultures from this continent. In this context, the general goal of the present study was to investigate the three dimensions of social representation theory, the representational field, the information and the attitude of the two conditions of edible flowers: a more general "food made with flowers" and more directional product "yoghurt made with flowers", using Brazilian consumers. To achieve this goal, a free word association task was applied. A total of 549 consumers participated in this study. Participants were divided into two conditions, in which the inductor expressions for the free word association task changed: (a) food products made with flowers and (b) yoghurt made with flowers . Results showed a very positive attitude to both situations, and consumers associated Food products made with flowers to "health care" while the central core of yoghurt made with flowers reflected the innovative condition of this product, supported here by their unpredictable character ( information generated). Graphical abstract: Highlights: Social representation of food made with flowers contains the word healthy, as core element. Different, exotic and novelty are important categories associated to food with flowers. Social representation of yoghurt made with flowers contains as main words novelty product and unexpected. Overall, Brazilian consumers have a positive attitude towards food products with flowers.